2016
DOI: 10.1111/1748-8583.12111
|View full text |Cite
|
Sign up to set email alerts
|

Buying into the ‘good worker’ rhetoric or being as good as they need to be? The effort bargaining process of new migrant workers

Abstract: A great deal of attention in the literature has focused upon employers' stereotypical perceptions of Central and Eastern European workers as ‘good workers’, and the impact such views have on hiring processes in low‐skilled employment. Drawing on multiple case studies, this paper examines the good worker rhetoric through the lens of the effort bargaining process and hard HRM strategies that target marginalised workers in the labour market. In particular, the extent to which migrant workers buy into the rhetoric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The assumption here is that complexity is a negative component of psychosocial job quality and it may be for persons who are being asked to perform tasks with a complexity that is not commensurate with their skill level (and/or ability to attain the necessary skill level). A study based in Scotland found that highly skilled migrant workers get segmented into low skilled jobs with bullying and racial discrimination [ 59 ]. However, for migrant workers who are in jobs commensurate with their skill level, complexity may not be perceived as a negative component of job quality.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption here is that complexity is a negative component of psychosocial job quality and it may be for persons who are being asked to perform tasks with a complexity that is not commensurate with their skill level (and/or ability to attain the necessary skill level). A study based in Scotland found that highly skilled migrant workers get segmented into low skilled jobs with bullying and racial discrimination [ 59 ]. However, for migrant workers who are in jobs commensurate with their skill level, complexity may not be perceived as a negative component of job quality.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that such an extension asks more of employers, but that existing evidence suggests that employers are often only weakly embedded in ALMP. This may be a particularly pertinent challenge in the UK given the institutional framework associated with the prevailing liberal market economy characterised by limited labour market regulation (Davies and Freedland, ; Baxter‐Reid, ). This regime differs from coordinated market economies and Nordic regimes, characterised by greater involvement of social partners on employment standards.…”
Section: Introductionmentioning
confidence: 99%
“…Employer perceptions that, compared to local workers, migrants are more reliable, more temporally flexible and have a stronger work ethic have been identified in studies of industries characterised by lower job quality, such as hospitality, retail, construction and agriculture (e.g. Baxter-Reid, 2016; MacKenzie and Forde, 2009; Moriarty et al, 2012; Ruhs and Anderson, 2010). Employers in these industries typically face challenges in attracting and retaining committed and motivated workers within the local labour market (Knox et al, 2015).…”
Section: Human Capital Perspectives On Employer Recruitment Of Temmentioning
confidence: 99%